Analysis of Village Income Dependence on Funds Government Transfers: A Case Study in Sukandebi Village - Anwar Fadly Sitepu; Isnaini Harahap; Sugianto (LP2M IAIN Palopo, 2026)
This study discusses the phenomenon of Sukandebi Village's income dependence on government transfer funds, which has increased significantly following the implementation of Law Number 6 of 2014 concerning Villages. The purpose of this study is to analyze the level of fiscal dependence of the village during the 2023–2025 period and to identify the factors causing the drastic decline in Village Original Income (PADes). The research employs a quantitative approach with a descriptive case study design, using secondary data derived from the Budget Realization Reports (APBDes and LRA) of Sukandebi Village. Data analysis was conducted through descriptive statistics and the calculation of the fiscal dependence ratio. The results show that the village's fiscal dependence increased from 92.91% in 2023 to 98.65% in 2025, accompanied by a decline in PADes from IDR 71 million (2023) to IDR 13 million (2025). These findings indicate the dominance of transfer funds, which has triggered a flypaper effect, as well as weak asset management and the absence of a Village-Owned Enterprise (BUMDes). The implications of this study emphasize the need for income diversification strategies, optimization of local potential, and capacity building for village officials to achieve sustainable fiscal independence.